2014
DOI: 10.1002/pssa.201431222
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive assessment of ZnO:Al window layers in advanced Cu(In,Ga)Se2photovoltaic technologies

Abstract: The increasing importance of the Cu(In,Ga)Se2 based thin films photovoltaic industry claims for the development of new assessment and monitoring tools to answer the needs existing in the improvement of the control of the processes involved in the production of solar cells modules. In this frame, a strong interest has been given to the development methodologies for the assessment of the CIGS absorber, nevertheless advanced optical tools for the characterization of the other layers in the solar cells are still m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 15 publications
4
16
0
Order By: Relevance
“…Some weaker contributions at lower wavenumber of the fundamental and higher orders of the LO peak can also be seen. These are attributed to multi-phonon peaks, which have also been previously observed in doped ZnO layers 13 , 27 . Their appearance is likely related to the presence of lattice defects 27 .…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Some weaker contributions at lower wavenumber of the fundamental and higher orders of the LO peak can also be seen. These are attributed to multi-phonon peaks, which have also been previously observed in doped ZnO layers 13 , 27 . Their appearance is likely related to the presence of lattice defects 27 .…”
Section: Resultssupporting
confidence: 74%
“…For these applications, optical spectroscopy based on Raman scattering has already proved its versatility for controlling various important material parameters of the stacks used in thin film solar cells, including crystallinity 8 , absorber and buffer composition 9, 10 , buffer layer thickness 8 , presence of secondary interfacial phases 11, 12 and doping concentration 13 in separate layers, as well as complete devices 8 . This includes also the use of resonant Raman strategies for the high sensitivity assessment of nanometric layers and interfacial regions in the device structure.…”
Section: Introductionmentioning
confidence: 99%
“…42 It has been reported that when ZnO is doped with Al, an additional contribution at around 510 cm -1 appears and the intensity of this defect-related peak is correlated to the conductivity of ZnO:Al thin films: the more conductive the AZO film, the higher the intensity of the defect-related peak. 43,44 The same trend is observed here for ZnO:Ti films as shown in Figure 3a where indeed an additional contribution at 518 cm -1 is clearly visible. The peak intensity is lower for the TZO film of sequence B, which is consistent with its sheet resistance being higher than that of sequence A.…”
Section: Influence Of the Sequence Of Precursor Introductionsupporting
confidence: 85%
“…Under this excitation condition, an intense LO-like peak located at ~570 cm -1 together with a so-called defect band in the range of 350-525 cm -1 (shaded in rectangular) is clearly present in Al doped ZnO thin films. The relative intensity of this defect band has been found to correlate with the resistivity of AZO thin films: the more resistive of the AZO, the lower intensity of this defect band [36,37]. This feature of the defect band is related to the interaction of the phonons with the free electron plasma, otherwise called phonon-plasmon coupling effect [38,39].…”
Section: Determination Of the Optimal Thickness Of Ald-al2o3mentioning
confidence: 99%